Multiple View Interactive Environment to Analyze Software Product Line Tools - Constantino, Kattiana; Figueiredo, Eduardo; Carneiro, Glauco; Minardi, Raquel (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2016: Anais do XII Simpósio Brasileiro de Sistemas de Informação, 2016)
Software Product Line (SPL) relies on the development of a collection of information systems from a shared set of software assets. In this context, the adoption of SPL in the industry relies heavily on tool support. This paper presents ViSPLatform, a visualization environment aimed at portraying data related to experiments focusing on SPL tools. We conducted a preliminary evaluation to analyze to which extent the platform is effective to support the understanding of characteristics of the SPL tools. The results of this study show that ViSPLatform can somehow indicate strengths and improvement opportunities in the analyzed SPL tools. For instance, they show that Automatic Analysis is a strength of the SPLOT tool and that Interface is an improvement opportunity. (Better if read in colors).